Evaluation of Environmental Regulations in Reducing Natural Resource Degradation in Protected Forest Areas - Fajri, Fajri; Riyadi, Agus; Ananta, Sabri (Adaptive Governance Research, 2025)
Purpose: This study examines the effectiveness of environmental regulations in reducing natural resource degradation in protected forest areas of South Sulawesi, Indonesia, focusing on governance challenges and implementation gaps. Subjects and Methods: A qualitative multiple-case study approach was employed, using data from 20 informants, policy documents, and field observations. The data were analyzed through thematic analysis supported by NVivo to identify key governance patterns. Results: The findings reveal that regulatory effectiveness is constrained by interconnected factors, including limited institutional capacity, governance fragmentation, reactive enforcement systems, socio-economic dependency on forest resources, and weak stakeholder coordination. These challenges demonstrate that environmental regulations function more as formal frameworks than as operational tools, reflecting a persistent policy–implementation gap. The discussion emphasizes the need for adaptive governance, stronger institutional capacity, integrated coordination mechanisms, and inclusive participation aligned with local socio-economic conditions. Conclusions: The study concludes that improving regulatory effectiveness requires shifting from rule-based approaches toward context-sensitive and collaborative governance models, while future research should expand comparative and interdisciplinary perspectives to strengthen environmental policy implementation.